2022
DOI: 10.1007/s00360-022-01456-3
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional state variations in a tropical seabird throughout its breeding season

Abstract: Individual body condition is frequently used to explain differences in foraging and breeding ecology in seabirds. However, little is known about the covariations of body mass with the nutritional state of animals as measured through plasma metabolites and how these different measures vary between and within individuals during breeding. Here, we assessed intra-individual variations of plasma metabolites (triglycerides, cholesterol, protein, and ß-hydroxybutyrate concentrations) and in body mass of Blue-footed b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Female masked boobies lay two eggs (Lerma, Serratosa, et al., 2020 ), whereas red‐footed boobies only lay one (Lormee et al., 2005 ). Female masked boobies might thus have higher nutritional demands (Lerma et al., 2022 ; Machovsky‐Capuska et al., 2016 ) and adapt their foraging to compensate for their initial investment in reproduction. Fourth, we studied incubating individuals, but most studies found differences during the chick‐rearing period, particularly for red‐footed boobies.…”
Section: Discussionmentioning
confidence: 99%
“…Female masked boobies lay two eggs (Lerma, Serratosa, et al., 2020 ), whereas red‐footed boobies only lay one (Lormee et al., 2005 ). Female masked boobies might thus have higher nutritional demands (Lerma et al., 2022 ; Machovsky‐Capuska et al., 2016 ) and adapt their foraging to compensate for their initial investment in reproduction. Fourth, we studied incubating individuals, but most studies found differences during the chick‐rearing period, particularly for red‐footed boobies.…”
Section: Discussionmentioning
confidence: 99%